2023
DOI: 10.1101/2023.03.06.531389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virus diversity and activity is driven by snowmelt and host dynamics in a high-altitude watershed soil ecosystem

Abstract: Viruses, including phages, impact nearly all organisms on Earth, including microbial communities and their associated biogeochemical processes. In soils, highly diverse viral communities have been identified, with a global distribution seemingly driven by multiple biotic and abiotic factors, especially soil temperature and moisture. However, our current understanding of the stability of soil viral communities across time, and their response to strong seasonal change in environmental parameters remains limited.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…Here, the recovered intertidal viruses were observed to infect almost all microbial lineages. Previous work has demonstrated that the variations of virus-host relationships across space and through time may reflect the degree of responses to environmental factors [32][33][34] . Consistent with these findings, the VHRs of different host lineages in intertidal zones were associated with multiple environmental factors, especially temperature, suggesting that seasonal changes were important in driving virus-host relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the recovered intertidal viruses were observed to infect almost all microbial lineages. Previous work has demonstrated that the variations of virus-host relationships across space and through time may reflect the degree of responses to environmental factors [32][33][34] . Consistent with these findings, the VHRs of different host lineages in intertidal zones were associated with multiple environmental factors, especially temperature, suggesting that seasonal changes were important in driving virus-host relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Viruses have been detected during mid-winter in Lake Erie (35,36), but there has been no comprehensive characterization of winter virus activity in the Great Lakes. Viruses are likely affected by ice cover extent as ice can shape host population structure (37)(38)(39) in addition to there being other ice cover-dependent factors (e.g., UV exposure and decay rates (40, 41)) that are intrinsically linked to viral activity as well. Lakes are sentinels of climate change (13), and Lake Erie represents a unique model environment for investigating how climate change manifests through ice cover extent.…”
Section: Introductionmentioning
confidence: 99%